Identification of Recurrent Insertions and Deletions in Exon 18 and 19 of Human Epidermal Growth Factor Receptor 2 as Potential Drivers in Non–Small-Cell Lung Cancer and Other Cancer Types. (16th February 2022) - Yin, Yan; Song, Lijie; Shi, Dongsheng; Liu, Bin; Li, Xiangke; Yang, Minjie; Liu, Bihao; Wang, Dejuan; Qin, Jianwen
Abstract : PURPOSE: Human epidermal growth factor receptor 2 (HER2) belongs to the same family as epidermal growth factor receptor (EGFR) and is known as an important cancer driver gene. Insertions and deletions (indels) are frequent driver mutations in both EGFR and HER2. The most common HER2 indels are the exon 20 insertions within the kinase domain, while others are rarely reported. Our study aimed to investigate other indels of HER2 that may act as driver mutations in Chinese patients with different cancer types. METHODS: In this retrospective study, patient samples were subjected to targeted sequencing covering HER2 and other cancer-related genes. Mutation profiles of patients harboring HER2 exon 18/19 indels were described. Identified HER2 exon 18/19 indels in our study were compared with external data from COSMIC. In silico and in vitro analyses were performed on selected indels of HER2 exon 18 and 19, respectively. RESULTS: A total of 25 indels in HER2 exon 18/19, 17 of which being recurrent, were identified in 20 of 53, 591 patients with lung cancer (0.037%), two of 5, 888 patients with colorectal cancer (0.034%), two of 3, 774 patients with breast cancer (0.053%), and one of 14 patients with urothelial carcinoma of the renal pelvis (7.1%). Most patients harboring HER2 exon 18/19 indels were absent of known driver mutations. In lung cancer, mutation profiles were comparable between patients carrying HER2 exon 18/19 indels and the two established HER2 drivers (exon 20 insertions and S310 mutations). The in silico and in vitro analyses suggested an activated state conferred by HER2 exon 18/19 indels, which could be targeted by different tyrosine kinase inhibitors. CONCLUSION: Our study revealed a class of rare but unique indels in HER2 exon 18/19, which may act as driver mutations in several cancer types. Abstract :